PROTOTYPE OF TODDLER HEIGHT AND WEIGHT MEASURING DEVICE USING IoT. - Ikmah, Maghfiroh Nur; Hidayat, Anjar Taufik; Wibisono, Gunawan (Journal of Electronic and Electrical Power Applications, 2024)
The application of IoT is needed to help human tasks, including in the health sector. For example, at the posyandu in previous habits of posyandu officers when measuring height and weight still use conventional equipment. and weight still use conventional equipment, the results also take a lot of time. Through these problems, this research makes a height and weight tool using a Load Cell sensor and an ultrasonic sensor that will be based on the Internet of Things. will be based on the Internet of Things with display of numeric data that appears on the Telkom IoT Platform and on the LCD. Designer tool consists of NodeMcu ESP32 as data processing, ultrasonic sensor (height), Load Cell sensor (weight), and LCD. (height), Load Cell sensor (weight) then the database will be stored in the body) then the database will be stored on the Telkom IoT Platform. For the results of 40 height experiments, the average error and accuracy values are 1.68% and 98.32%. For the average results of 40 weight trials, an error value of 1.85% and an accuracy value of 98.42% were obtained. The results for the calculation of the user assessment scale obtained a result of 35.75 which means the tool is quite good.